Variability of microbiomes in winter rye, wheat, and triticale affected by snow mold: predicting promising microorganisms for the disease control - Ildar T. Sakhabutdinov; Inna B. Chastukhina; Egor A. Ryazanov; Sergey N. Ponomarev; Olga A. Gogoleva; Alexander S. Balkin; Viktor N. Korzun; Mira L. Ponomareva; Vladimir Y. Gorshkov (Environmental Microbiome)
Abstract Background Snow mold caused by different psychrophilic phytopathogenic fungi is a devastating disease of winter cereals. The variability of the snow mold pathocomplex (the quantitative composition of snow mold fungi) has not been evaluated across different crops or different agrocenoses, and no microbial taxa have been predicted at the whole-microbiome level as potential effective snow mold control agents. Our study aimed to assess the variability of the snow mold pathocomplex in different winter cereal crops (rye, wheat, and triticale) in different agrocenoses following the peak disease progression and to arrange a hierarchical list of microbial taxa predicted to be the main candidates to prevent or, conversely, stimulate the development of snow mold pathogens. Results The variability of microbiomes between different crops within a particular agrocenosis was largely determined by fungal communities, whereas the variability of microbiomes of a particular crop in different agrocenoses was largely determined by bacterial communities. The snow mold pathocomplex was the most “constant” in rye, with the lowest level of between-replicate variability and between-agrocenoses variability and (similar to the triticale snow mold pathocomplex) strong dominance of Microdochium over other snow mold fungi. The wheat snow mold pathocomplex was represented by different snow mold fungi, including poorly investigated Phoma sclerotioides. To predict snow mold-control microorganisms, a conveyor of statistical methods was formed and applied; this conveyor enables considering not only the correlation between the abundance of target taxa and a phytopathogen but also the stability and fitness of taxa within plant-associated communities and the reproducibility of the predicted effect of taxa under different conditions. This conveyor can be widely used to search for biological agents against various plant infectious diseases. Conclusions The top indicator microbial taxa for winter wheat and rye following the winter period were Ph. sclerotioides and Microdochium, respectively, both of which are causal agents of snow mold disease. Bacteria from the Cellulomonas, Lechevalieria, and Pseudoxanthomonas genera and fungi from the Cladosporium, Entimomentora, Pseudogymnoascus, and Cistella genera are prime candidates for testing their plant-protective properties against Microdochium-induced snow mold disease and for further use in agricultural practice.